Valorization of by-products from vegetable oil industries: Enzymes production by Yarrowia lipolytica through solid state fermentation - Costa, Ana Rita; Salgado, José Manuel; Lopes, Marlene; Belo, Isabel (Frontiers in Sustainable Food Systems, 2022)
Vegetable oil extraction generates high amounts of by-products, which are designated as oil cakes. Since the current strategies employed for oil cakes’ reuse are linked with some drawbacks, identification of alternative approaches to decrease the environmental impact and promote a circular economy is of vital importance. In general, these materials are characterized by high fibre content, making them suitable to be employed in solid state fermentation (SSF). Filamentous fungi have been the microorganisms mostly applied in SSF and yeasts were applied in less extent. In the present work, three by-products from the extraction of olive, sunflower and rapeseed oils were used as solid substrates in SSF for lipase and protease production by Yarrowia lipolytica W29. Oil cakes mixtures composition was optimized for the production of each enzyme using a simplex-centroid design of experiments. A 50 % (w/w) mixture of olive and sunflower cakes led to the highest lipase production, while a combination of the three oil cakes was most suitable for maximum protease production. Both enzymes were produced at maximum levels in a short period of 48 h. This work demonstrated that enzyme production by Y. lipolytica W29 in SSF can be modulated by the different combinations of oil cakes in the substrate mixture. Additionally, the potential of using by-products from vegetable oil industries in SSF processes was also demonstrated, showing alternative strategies for their revalorization.